2008
DOI: 10.1002/jnr.21715
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of hippocampus following perinatal asphyxia: Effects on postnatal apoptosis and neurogenesis

Abstract: Asphyxia during delivery produces long-term deficits in brain development, including hippocampus. We investigated hippocampal plasticity after perinatal asphyxia, measuring postnatal apoptosis and neurogenesis. Asphyxia was performed by immersing rat fetuses with uterine horns removed from ready-to-deliver rats into a water bath for 20 min. Caesarean-delivered pups were used as controls. The animals were euthanized 1 week or 1 month after birth. Apoptotic nuclear morphology and DNA breaks were assessed by Hoec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 104 publications
2
57
0
3
Order By: Relevance
“…Neuroprotection elicited by intracerebroventrical administration of BDNF to postnatal day 7 rat pups was causally linked to pronounced and rapid increases in the phosphorylation/activation of ERK and Akt kinases lasting up to at least 12 h. Furthermore, ERK activation was specifically shown to reduce apoptotic neuronal death assessed with cleaved caspase 3 immunohistochemistry [13]. In addition to BDNF, other growth factors such as basic fibroblast growth factor have been identified as a factor promoting cell survival and neurogenesis, through activation of the ERK pathway [25,26]. In addition, Cohen-Armon et al demonstrated that ERK2 phosphorylation can be modulated by PolyADP-ribose polymerase-1 (PARP-1) which catalyze a posttranslational modification of nuclear proteins by polyADP-ribosylation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotection elicited by intracerebroventrical administration of BDNF to postnatal day 7 rat pups was causally linked to pronounced and rapid increases in the phosphorylation/activation of ERK and Akt kinases lasting up to at least 12 h. Furthermore, ERK activation was specifically shown to reduce apoptotic neuronal death assessed with cleaved caspase 3 immunohistochemistry [13]. In addition to BDNF, other growth factors such as basic fibroblast growth factor have been identified as a factor promoting cell survival and neurogenesis, through activation of the ERK pathway [25,26]. In addition, Cohen-Armon et al demonstrated that ERK2 phosphorylation can be modulated by PolyADP-ribose polymerase-1 (PARP-1) which catalyze a posttranslational modification of nuclear proteins by polyADP-ribosylation [27].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent finding in rodent models of neonatal hypoxia-ischemia or asphyxia and adult stroke is the increase in cell proliferation and neurogenesis in hippocampus (Daval and Vert 2004;Bartley, Soltau et al 2005;Pourie, Blaise et al 2006;Morales, Fiedler et al 2008;Geibig, Keiner et al 2012). In these studies, hippocampal neurogenesis was assessed at different time points compared to our study, such as 1 week after perinatal asphyxia (Morales, Fiedler et al 2008) or 3, 10 and 35 days after hypoxia-ischemia (Bartley, Soltau et al 2005) or different degrees of hypoxia were used (Daval and Vert 2004;Pourie, Blaise et al 2006). However, our results showed a decrease of BrdU-labelled cells in the dentate gyrus of hippocampus at P60 after neonatal anoxia, what reflects on diminished neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, the most frequently used are the Rice-Vannucci hypoxia-ischemia (Rice, Vannucci et al 1981) and the perinatal asphyxia models (Bjelke, Andersson et al 1991). The first is induced unilaterally in 7-day-old rats, and the latter consisted by the immersion of uterus containing the ready-to-deliver fetuses in saline at 37 °C for 19-20 minutes (Morales, Fiedler et al 2008;Galeano, Blanco Calvo et al 2011). The neonatal anoxia model was first described by Dell'Anna and colleagues (Dell'Anna, Calzolari et al 1991) and was modified and validated by our group (Takada, Sampaio et al 2011), which consists in the exposure of 30-hours-old rats to 100% nitrogen gas during 25 minutes at 37 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that the chronic placental insufficiency (CPI) or umbilical cord occlusion to which fetus may be exposed to result in fatal hypoxenima [22] leading to synaptic dysfunction that triggers damage in neonates resulting in neurodegeneration [23]. Maternal hormonal disturbances also have adverse effect on fetus.…”
Section: Introductionmentioning
confidence: 99%